ANALYSIS OF GEOMORPHOLOGICAL ASPECTS OF SURADE SUB-DISTRICT, SUKABUMI DISTRICT, WEST JAVA - Firmansyah, Yusi; Khoirullah, Nur; Fahrul Yahya, Moh (Journal of Geological Sciences and Applied Geology, 2023)
The current form of the earth's surface romance is the result of geological processes that have taken place during the geological period which can show how the characteristics and distribution of the constituent rocks. This research was conducted to find out how the geomorphological conditions by analyzing the aspects of morphography, morphometry, and morphogenetics as a form of geomorphology in an area. The research location is in Mekarjaya Village, Ciemas Sub-district, Sukabumi Regency, West Java, which has geomorphological conditions influenced by the activity of an old submarine volcano which was then uplifted and experienced an intensive tectonic process. The method used in this study combines qualitative and quantitative aspects supported by satellite imagery, data processing applications, and references from previous research results. The results of this study show that there are 2 geomorphological units, namely the Slightly Steep Volcanic Hills Unit and the Steep Volcanic Hills Unit with the distribution of andesitic lava and volcanic breccia rocks. The drainage pattern that develops is rectangular.